Acoustic Emissions versus Pressure Stimulated Currents during bending of restored marble epistyles: Preliminary results (Fracture and Structural Integrity, 2017)
The efficiency of two modern sensing techniques, namely the “Acoustic Emissions” and the “Pressure Stimulated Currents” ones, when they are used as Continuous Structural Health Monitoring tools, is assessed experimentally. The protocol includes multi-point bending of an accurate copy of a fractured marble epistyle of the Parthenon’s Temple on the Acropolis of Athens, under a scale of 1:3. The integrity of the epistyle is restored with three pairs of bolted titanium bars, according to the pioneering technique developed by the scientists of the “Committee for the Conservation of the Acropolis Monuments”. The data provided by the above techniques are considered in juxtaposition to each other and also in comparison to data provided by the “Digital Image Correlation” technique. It is concluded that, at least from a qualitative point of view, the data of all three techniques are in good mutual agreement. Combined exploitation of the various sets of experimental data enlightens interesting aspects concerning the succession of failure mechanisms activated during the loading procedure, revealing the critical role of the internal interfaces characterizing the restored epistyle. Moreover it is definitely indicated that both the “Acoustic Emissions” and the “Pressure Stimulated Currents” techniques provide clear signs of upcoming failure well before macroscopically visible damages are detected at the external surface of the specimen.
Keywords: Acoustic Emissions; Pressure Stimulated Currents; Digital Image Correlation; Marble Monuments; Restoration/Conservation; Continuous Structural Health Monitoring